The Influence of Play Environment Arrangement on Children's Creativity - Wira Tata Raya; Nurul Fadilah Batubara; Irma Said; Mira Angrilla; Rika Sepriani; Irma Yuliantina (Universitas Panca Sakti Bekasi, 2024)
Creativity is one of the most important aspects in early childhood development. There are many factors that influence early childhood creativity. This research aims to determine the influence of the arrangement of the play environment on the creativity of young children with the factors that influence it. This research uses a descriptive qualitative research method by presenting the data as it is without manipulation or other treatments. The aim of this research is to present a complete picture of an event or is intended to expose and clarify a phenomenon that occurs. The results of research on 50 PAUD units with students aged 4-6 years show that the arrangement of the play environment influences children's creativity. A challenging, varied and fun play environment can stimulate children's cognitive, social, emotional and physical development, as well as provide opportunities for children to explore, imagine and innovate. Arranging a play environment that accommodates several play activities prepared by the teacher encourages children to carry out play activities that suit the child's needs, interests and talents, so that it can increase children's creativity. The use of various tools and materials sourced from the surrounding environment encourages children to create works according to their imagination. An attractive play environment creates a higher level of curiosity in children. Research shows that there is an increase in fluency of thinking, flexibility of thinking, originality, elaboration which is shown by children's work which varies according to their respective interests. This shows an increase in creativity after the teacher arranges the play environment